2016
DOI: 10.1186/s40850-016-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Body condition scoring of Bornean banteng in logged forests

Abstract: Background: The Bornean banteng (Bos javanicus lowi) is an endangered subspecies that often inhabits logged forest; however very little is known about the effects of logging on their ecology, despite the differing effects this has on other ungulate species. A body condition scoring system was created for the Bornean banteng using camera trap photographs from five forests in Sabah, Malaysia, with various past and present management combinations to establish if banteng nutrition suffered as a result of forest di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The visual features of each body compositions captured by camera trap can be used to investigate the development of BCS in banteng. The BCS assessment was previously recommended for use to investigate Bornean banteng (Bos javanicus lowi) in logging forests in Sabah, Malaysia (Prosser et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The visual features of each body compositions captured by camera trap can be used to investigate the development of BCS in banteng. The BCS assessment was previously recommended for use to investigate Bornean banteng (Bos javanicus lowi) in logging forests in Sabah, Malaysia (Prosser et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only sufficiently visible images which showed the whole body of the animal were selected for scoring. The visual body condition of banteng was scored by a five-points pictorial scoring system developed from scoring indexes of Bornean banteng (Prosser et al, 2016) and Bali cattle (Soares & Dryden, 2011). Each individual was given a score in the appearance of seven key areas of its body.…”
Section: Body Condition Scoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Logging increases the abundance of pioneer species (Imai et al 2012), in cluding grasses, vines and shrubs favourable to banteng (S. Ridge unpubl. data), and regenerating vegetation benefits banteng body condition and breeding (Gardner et al 2014, Prosser et al 2016, which is likely to have influenced the larger herds observed in forest with < 8 yr of PLR. Reduced disturbance from heavy machinery in the years following logging activity may have helped herds re-form and allowed herds to aggregate more frequent ly.…”
Section: Banteng Herd Sizesmentioning
confidence: 99%
“…Increased anthropogenic disturbance may cause herds to separate and also in crease stress levels, which is likely to impact banteng breeding activity and behaviour (Gardner et al 2014). Furthermore, B. j. lowi have reduced body conditions in conventionally logged forests compared to reduced-impact logging (RIL) forests (Prosser et al 2016).…”
Section: Introductionmentioning
confidence: 99%